Characteristics research of low-temperature heat pipes for energy-saving equipment - Шаповал, Андрей Андреевич; Стрельцова, Юлия Валерьевна (Technology audit and production reserves, 2016)
The efficiency of the heat pipes (HP) is largely dependent on the characteristics of capillary structures (CS) used therein. Due to the composite materials developed in Institute for Problems in Materials Science (IPMS) of NAS of Ukraine, which were used as the CS, Ukrainian heat pipes with high hydrodynamic and thermal characteristics were developed. The aim of the experimental work of the authors was the comparison of thermal characteristics of heat pipes that are based on composite porous structures with similar HP characteristics with fiber porous structures (which are considered to be the most effective view of insert HP). The results showed that HP with composite CS provides better thermal characteristics, especially when the heating of pipes was from the top, and cooling – from the bottom. In this position, a composite HP with CS steadily functioned under heat load up to 25 watts, whereas HP with fiber CS stopped stable operation at a load of 15 watts. As with the horizontal and vertical arrangement of the pipe (at «below» heat input), the value of thermal resistance (R [K/W]) for pipes with composite CS did not exceed values R that are typical for HP with fiber porous structures. Thus, thanks to the authors, it was found that the new composite structure is more appropriate to use when placing the HP at an angle to the "upper" heat supply than fiber HP.